COLLECTING AND ORGANIZING IDEAS: THE USE OF CLUSTERING TECHNIQUE IN WRITING NARRATIVE TEXT - DEWI, Hilda krisna, - (2010)
The present research was conducted to investigate the use of clustering technique in writing narrative text. A quasi experiment with pre-test and post-test design was employed. It involved two classes of eighth graders in a junior high school in Subang which was purposively selected. Data were obtained through pre-test, post-test, and interview. Georgia Writing Assessment was selected to assess students' writing. Findings were analyzed by using t-test and Rico's theories on clustering technique. The research demonstrated that clustering technique improves students' ability in writing narrative text on generating and organizing ideas of story (tobt > tcrit, 3.705 > 2.000, r = 0.472). In addition, this technique proposes fun learning, increases motivation, comprehends the topic, challenges creativity, facilitates interactions, provides simple construction, and serves new simple technique to write. An appropriate technique of writing will help students compose a piece more easily. Moreover, teachers need to rehearse themselves in utilizing the technique of writing; hence they can give a clear guidance for the students. Combination between a good technique and skillful teacher will serve valuable contribution to improve students' writing ability. Key words : clustering technique, narrative text, teaching, writing.